1981
DOI: 10.1021/np50017a013
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antitumor Agents. XVII. Physalin B and 25,26-Epidihydrophysalin C From Witheringia coccoloboides

Abstract: An investigation of Witheringia coccoloboides (Dammer) A. T. Hunziker [Capsicum fuscoviolaceum (Cufodontis) Mort. And Standl.] roots has resulted in the isolation of two cytotoxic compounds: physalin B (1) and a novel physalin, which was characterized by spectral analysis as 25,26-epidihydrophysalin C (2). Both compounds have demonstrated cytotoxic activity in 9KB and 9PS tumor cells (in vitro). Physalin B (1) has demonstrated moderate activity against the 3PS mouse leukemia (in vivo).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 2 publications
1
34
0
Order By: Relevance
“…Compound 4a obtained by the hydrogenation of 4 was weaker than all the others, and compound 5 had no activity at the concentrations tested. Previous studies had already demonstrated that 2 and 3, but not 1, 4 and 5, were cytotoxic to tumor cell lines in vitro [9][10][11]19,20]. Thus, As mentioned before, previous studies of the biological activity of physalins led to the conclusion that the presence of the conjugated cyclohexenone moiety is essential for cytotoxicity [9,12].…”
Section: Biological Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Compound 4a obtained by the hydrogenation of 4 was weaker than all the others, and compound 5 had no activity at the concentrations tested. Previous studies had already demonstrated that 2 and 3, but not 1, 4 and 5, were cytotoxic to tumor cell lines in vitro [9][10][11]19,20]. Thus, As mentioned before, previous studies of the biological activity of physalins led to the conclusion that the presence of the conjugated cyclohexenone moiety is essential for cytotoxicity [9,12].…”
Section: Biological Resultsmentioning
confidence: 84%
“…Based on these studies, it has been postulated that the presence of the double bond between C-2 and C-3 (ring A) is a fundamental chemical feature responsible for those actions [9,12,20]. In addition, Antoun et al [20] demonstrated that the 5,6-epoxy ring of physalins is also responsible for antitumor activity, and Lee and Houngton [19] recently reinforced the importance of the functional groups located at C-5 and C-6 as well. However, it seems that the structure requirements for cytotoxic activity are far from being decisively elucidated.…”
mentioning
confidence: 99%
“…The positive control tested was rifampicin which has an MIC value of 0.2 mg/mL. The overall results suggested that the main compound in the fraction A1-29-12, which showed the antimycobacterial activity, is physalin D. Concerning the cytotoxic activity physalin B presents high activity (ID 50 0.32-0.35 mg/mL) against mouse tumour cells (Antoun et al, 1981). As far as we know, there is a lack of scientific evidence about the cytotoxicity of physalin D.…”
Section: Antimycobacterial Physalins 447mentioning
confidence: 96%
“…26,27 Compound 1 (64 mg): the electrospray ionization mass spectrometry (ESIMS) showed a molecular ion at m/z 533. …”
Section: Structural Determination Of Physalin B and Cmentioning
confidence: 99%